United Nations’ Stabilisation Mission in Mali: The Politics and Emerging Challenges - ODDIH, Mike C.; EMESIBE, Vincent Obiora (Socialscientia: Journal of Social Sciences and Humanities, 2022)
This paper examined the United Nations stabilization mission in Mali, the politics of its adoption and emerging challenges. The data were generated through interviews complemented with literature. It employed Critical Theory of Robert Cox and thematic method in its analysis. The findings indicate that the mandate was adopted through a process that subordinated the leadership role of United Nations Secretariat to the national interest of France in the face of incapacity of African stakeholders in Mali. The interplay of French dominance, geostrategic context of the Malian conflict and incapacity of African stakeholders, underlie the determination of the character and adoption of the stabilization mandate and its challenges in the field. United Nations should uphold its principle impartial, Promote local ownership of the peace process, local security and de-emphasises stabilisation operations in Mali. African stakeholders must strengthen their commitment to peace operations, buildup and sustain a functional Standby Force (ASF) for prompt responses and sustainable leadership in managing Conflicts in Africa.